Enhancing Conceptual Understanding of Plane Geometry through Tugu Yogyakarta Ethnomathematics Pop-Up Fourth-Grade - Nurma Tasya Ajeng Maulina; Syahda Nofa Sabrina; Karina Eka Septya; Ilzama Maula Wafda Sabila (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2025)
The abstract nature of geometry often creates a disconnect between mathematical concepts and students' daily lives, resulting in limited conceptual understanding in elementary education. This study aims to evaluate the effectiveness of an ethnomathematics-based pop-up book, centered on the Tugu Yogyakarta monument, in enhancing fourth-grade students' understanding of plane geometry. Using a quantitative, quasi-experimental, nonequivalent control-group design, the research involved 30 students at SD Netral C Yogyakarta, divided into an experimental and a control group. Data were collected via expert-validated multiple-choice tests and analyzed using descriptive and inferential statistics, including the Independent Sample t-Test. Results indicated that the data were normally distributed and homogeneous (p = 0.441). The Independent Sample t-Test yielded a t-count of 3.028 with a significance of 0.004, leading to the rejection of the null hypothesis. These findings demonstrate that students who used the ethnomathematics pop-up book achieved significantly higher conceptual understanding than those who used conventional textbooks. The integration of 3D visual media and local cultural icons effectively bridges abstract geometric properties with concrete spatial visualization, making it a viable alternative for meaningful mathematics instruction in elementary schools.